Religionomik Hadits Al-Habbah As-Sauda’ (Studi Analisis Matan Hadis) - Muhamad Agus Mushodiq (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
This study aims to examine the hadith related to habbah sauda 'which serve as a justification tool of trade product quality. Given that many herbal medicine companies, especially habbatu sauda who use the verses of the Qur'an or hadith as a means of justification of the greatness of the drugs they sell. The use of disproportionate religious symbols will only lead to improper symbolization. This will result in misinterpretation of the content of the Qur'an or hadith. Thus the analysis of hadith matan with Fazlurrahman’s hermeneutics allegedly gave an ideal interpretation, logical and holistic. The analysis stages of matan hadith used are (1) linguistic analysis, (2) thematic analysis, (3) confirmatory analysis, (4) historical analysis, (5) general analysis, and (6) praxis analysis. As for results that found from this study are (1) the selection of dicsi syifa and not dawa indicates that in habbatus sauda there are substances that have healing properties, not drugs that are physically intact can cure all kinds of diseases. (2) with other traditions it is found that what is meant by all diseases is a disease of money arose in the time of the Prophet, not a generative disease that always evolved into the modern era, (3) Ibn Hajar al-Atsqalāni and Abu Bakar bin al- 'A'rabi says that honey is very clearly mentioned in the Qur'an as a drug more worthy of the title as a cure of all illness than al-habbah as-sauda